Assessment of variations in sphenoid sinus pneumatization in Indian population: A multidetector computed tomography study - Hiremath, Shivaprakash B; Gautam, Amol B; Sheeja, Keerthy; Benjamin, Geena (Indian Journal of Radiology and Imaging, 2018)
Background and Purpose: The purpose of our study was to assess the prevalence of variations in the extent of sphenoid pneumatization in the Indian population and compare with existing literature. Materials and Methods: This retrospective study included 500 patients who underwent CT of the paranasal sinuses. The multiplanar reformations of paranasal sinus were assessed for the type of pneumatization of the sphenoid sinus and type of clival, lateral recess, lesser wing, and anterior recess extensions. Results: The conchal, presellar, incomplete sellar, and complete sellar types comprised 0%, 1.2%, 22.2%, and 76.6% of patients. The extensions of pneumatization subtypes in the study population were clival in 76.6% subjects; lateral recess, lesser wing, and anterior recess in 59.7%, 20.4%, and 20.4% of sinuses, respectively. The pure forms were seen in 25.4% and combined forms in 61% of sinuses. The presellar type (1.2%) was less common and sellar type (98.8%) being common in our population compared to the Caucasian and East Asian population. The sphenoid sinuses were extensively pneumatized in our population compared to the Chinese and Caucasian population, the prevalence being 76.6%, 68%, and 44.5% for clival; 59.7%, 46%, and 28.3% for lateral recess; 20.4%, 32%, and 12% for lesser wing extension, respectively. The pure forms were relatively less common and combined forms being more common compared to the Chinese and Caucasian population in our study. Conclusion: The extent of pneumatization of the sphenoid sinus has clinical and surgical implications in sellar and central skull base lesions, and variability in different populations confirms that ethnicity influences the differences in prevalence.
Keywords: Anatomic variation; cerebrospinal fluid leak; idiopathic intracranial hypertension; pituitary tumors; sphenoid sinus; transnasal endoscopic surgery